Nutritional, physical and sensory characteristics of gluten-free biscuits incorporated with a novel resistant starch ingredient - Mariasole Cervini; Antonello Frustace; Guillermo Duserm Garrido; Gabriele Rocchetti; Gianluca Giuberti (Heliyon, 2021)
Gluten-free (GF) biscuits were prepared by replacing part of a GF flour mix (GFM) with 0, 15, 30 and 45 g/100 g (total flour) with a novel resistant starch-rich ingredient obtained from annealed white sorghum starch (RSWS). The chemical composition, physical characteristics, in vitro starch digestion and sensory evaluation of biscuits were considered. The chemical composition of samples was influenced by the addition of the RSWS. The highest total dietary fibre and RS contents (p < 0.05) were measured in 45-RSWS biscuits. The starch hydrolysis index values decreased when the level of RSWS increased in the composite. With regard to quality parameters, the use of RSWS influenced the hardness of the biscuits, and the highest value obtained for 45-RSWS. Some of the selected sensory attributes, along with the overall acceptability score, were negatively influenced by the RSWS addition, even if all remained above the limit of acceptability. The use of RSWS in GF biscuit formulation can contribute towards the creation of food products likely having slowly digestible starch properties, and this can be achieved without drastically compromising on the quality and sensory attributes.